The Use of Minimally Invasive Techniques in Spinal Surgery: Current Status and Future Directions: Minimally Invasive Techniques in Spinal Surgery - Haq, Mian Iftikhar ul; Saud, Abdul Munaf; Khan, Shaukat Hayat; Raza, Tauseef; Khan, Abdul Rehman; Abidi, Syed Abdur Rub (Pakistan Journal of Health Sciences, 2024)
Minimally invasive spine surgeries have come a long way from their open counterparts in recent years, allowing for less tissue stress, smaller incisions, and quicker recoveries. Objectives: To trace the development of minimally invasive spine surgical procedures from their inception to the present day and to find ways to improve and innovate these methods in the future. Methods: This prospective observational study was conducted at the Neurosurgery Department of Lady Reading Hospital-Medical Training Initiative, Peshawar. 230 individuals were progressively enrolled, and a plethora of spinal disorders were recruited as inclusion criteria. This information was gathered by painstakingly capturing demographics, co-morbidities, surgical procedure details and postoperative results. Statistical analysis identifies the trends. Results: The mean age of the study was 54.7 years and male were higher in numbers. Discectomy was the most commonly performed operation with the degenerative disease of the spine accounting for the highest (26.06%). With an average hospital stay of 5.8 days, problems such as Dural tears occurred during the operation in 10.87% of cases. While problems such neighboring segment illness were observed in 6.52% of patients, follow-up demonstrated improved functional results in 65.22% of cases. Variables such as surgical indication and procedure showed significant relationships (p<0.001) according to chi-square testing. Conclusions: It was concluded that minimally invasive spine surgery draws attention to the need for ongoing innovation and research to improve outcomes and overcome technical challenges in the treatment of complex spinal illnesses. This approach offers less invasive treatments with shorter recovery times and fewer complications